2017
DOI: 10.3390/ijms18030638
|View full text |Cite
|
Sign up to set email alerts
|

Is Ghrelin Synthesized in the Central Nervous System?

Abstract: Abstract:Ghrelin is an octanoylated peptide that acts via its specific receptor, the growth hormone secretagogue receptor type 1a (GHSR-1a), and regulates a vast variety of physiological functions. It is well established that ghrelin is predominantly synthesized by a distinct population of endocrine cells located within the gastric oxyntic mucosa. In addition, some studies have reported that ghrelin could also be synthesized in some brain regions, such as the hypothalamus. However, evidences of neuronal produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 114 publications
1
59
0
9
Order By: Relevance
“…We conclude that ghrelin is absent from the lumbosacral spinal cord. These data, although focused on the caudal spinal cord, are consistent with previous studies that indicate that ghrelin is absent from the CNS (Sakata et al 2009;Furness et al 2011;Kern et al 2014;Cabral et al 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We conclude that ghrelin is absent from the lumbosacral spinal cord. These data, although focused on the caudal spinal cord, are consistent with previous studies that indicate that ghrelin is absent from the CNS (Sakata et al 2009;Furness et al 2011;Kern et al 2014;Cabral et al 2017).…”
Section: Discussionsupporting
confidence: 92%
“…While these observations imply that GHSR1a is in the pathways of defecation control, ghrelin itself is not found in the mouse spinal cord (Furness et al 2011). In fact, it is probable that ghrelin is not present even in other parts of the central nervous system (Sakata et al 2009;Furness et al 2011;Kern et al 2014;Cabral et al 2017).…”
Section: Introductionmentioning
confidence: 90%
“…The circulating ghrelin produced in the stomach and intestines crosses the blood-brain barrier and acts on ARC-POMC neurons (Schaeffer et al 2013). However, it is uncertain whether ghrelin is synthetized at physiologically relevant levels in the central nervous system (Kojima et al 1999;Mondal et al 2005;Cabral et al 2017). We found that ablation of Ghsr1a eliminated the ghrelin-induced excitatory effect on AgRP/NPY neurons, indicating that Ghsr1a is essential for the excitatory effect of ghrelin on AgRP/NPY neurons.…”
Section: Discussionmentioning
confidence: 72%
“…; Cabral et al . ). We found that ablation of Ghsr1a eliminated the ghrelin‐induced excitatory effect on AgRP/NPY neurons, indicating that Ghsr1a is essential for the excitatory effect of ghrelin on AgRP/NPY neurons.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been reported that no ghrelin-specific staining is found and ghrelin receptor-expressing neurons do not have adjacent ghrelin immunoreactive terminals in the brain or spinal cord of the rat and mouse [40]. Recently, Cabral et al [41] provided a comprehensive review of all available data related to the distribution of ghrelin in the CNS and concluded that there are no indisputable and reliable evidences to support the idea that ghrelin is present in the brain at physiologically significant levels.…”
Section: Figmentioning
confidence: 99%